Economisation of non-government organizations - Wygnański, Jan Jakub (Journal of Public Governance, 2008)
The aim of the article is to describe the phenomenon of economisation of the non-government sector. As part of the process, traditional organisations perceived as non-profit ones engage in activities geared towards the generation of income from the sale of products and services. The article discusses the scale of the process, both nationally and internationally. In the case of the former, quantitative surveys conducted by the Klon/Jawor Association have been used. The Authors indicate reasons for which organisations may decide to embark on business activity as well as the risks associated with the decision to do so. Individual types of organisational resources important from the vantage point of their market position have also been analysed.